2016
DOI: 10.1002/ejoc.201600747
|View full text |Cite
|
Sign up to set email alerts
|

Glycosyl ortho‐Methoxybenzoates: Catalytically Activated Glycosyl Donors with an Easily Removable and Recyclable Leaving Group

Abstract: We describe the β‐ortho‐methoxybenzoate as a shelf stable and practical C‐1 nucleofuge for catalytic chemical glycosylation in which the benzoic acid by‐product can be easily removed, reisolated, and potentially recycled after the glycosylation reaction. This new type of glycosyl donor can be efficiently activated by a range of promoters, including Bi(OTf)3, Fe(OTf)3, TMSOTf (TMS = trimethylsilyl), and triflic acid, with low (<10 mol‐%) catalyst loadings. The donor shows higher reactivity than analogous benzoa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 66 publications
2
10
0
Order By: Relevance
“…Based on previous studies with anomeric benzoates as C-1 leaving groups, we have found that a second coordination center (o-OMe) significantly increases the glycosyl donor reactivity. 29 We wanted to explore whether a similar trend would be present among one of the most used glycosyl donor types, the thioglycosides.…”
supporting
confidence: 92%
See 2 more Smart Citations
“…Based on previous studies with anomeric benzoates as C-1 leaving groups, we have found that a second coordination center (o-OMe) significantly increases the glycosyl donor reactivity. 29 We wanted to explore whether a similar trend would be present among one of the most used glycosyl donor types, the thioglycosides.…”
supporting
confidence: 92%
“…In oligosaccharide synthesis, the glycosyl donor leaving group determines the mode of activation, which basically refers to the choice of Lewis acid (e.g., halophilic, thiophilic, hard or soft). Based on previous studies with anomeric benzoates as C-1 leaving groups, we have found that a second coordination center ( o -OMe) significantly increases the glycosyl donor reactivity . We wanted to explore whether a similar trend would be present among one of the most used glycosyl donor types, the thioglycosides.…”
supporting
confidence: 62%
See 1 more Smart Citation
“…1 . Of these, the most widely applied methods capitalize on reactions of glycosyl donors in which the C2 position is capped with a carbonyl-based participating group (e.g., OAc, OBz, NPhth) 7 10 . For example, activation of 2- O -acyl thioglycoside with an oxidant and triflate salt leads to the formation of the dioxolenium ion intermediate 4 which is quenched with an alcohol to provide glycoside 1 in high 1,2- trans selectivity (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Donor-regenerative glycosidations is an emerging trend in the chemical glycosidation field. The concept has been investigated by Demchenko using −OFox imidate donors, by Wan through an interrupted Pummerer reaction using 2-(2-propylthiol)­benzyl (PTB) glycosides and by Jensen utilizing o -methoxybenzoates.…”
Section: Resultsmentioning
confidence: 99%